Cyprinid herpesvirus 3 as a potential biological control agent for carp (Cyprinus carpio) in Australia: susceptibility of non‐target species. Issue 9 (27th December 2016) - McColl, K A; Sunarto, A; Slater, J; Bell, K; Asmus, M; Fulton, W; Hall, K; Brown, P; Gilligan, D; Hoad, J; Williams, L M; Crane, M St J
Abstract: Carp ( Cyprinus carpio L.) is a pest species in Australian waterways, and cyprinid herpesvirus 3 (CyHV‐3) is being considered as a potential biological control (biocontrol) agent. An important consideration for any such agent is its target specificity. In this study, the susceptibility to CyHV‐3 of a range of non‐target species (NTS) was tested. The NTS were as follows: 13 native Australian, and one introduced, fish species; a lamprey species; a crustacean; two native amphibian species (tadpole and mature stages); two native reptilian species; chickens; and laboratory mice. Animals were exposed to 100–1000 times the approximate minimum amount of CyHV‐3 required to cause disease in carp by intraperitoneal and/or bath challenge, and then examined clinically each day over the course of 28 days post‐challenge. There were no clinical signs, mortalities or histological evidence consistent with a viral infection in a wide taxonomic range of NTS. Furthermore, there was no molecular evidence of infection with CyHV‐3, and, in particular, all RT‐PCRs for viral mRNA were negative. As a consequence, the results encourage further investigation of CyHV‐3 as a potential biocontrol agent that is specific for carp.